The Clival Line as an Important Arachnoid Landmark During Endoscopic Third Ventriculostomy: An Anatomic Study - Kurucz, Peter; Barany, Laszlo; Buchfelder, Michael; Ganslandt, Oliver (World Neurosurgery, 2018)
OBJECTIVE: Endoscopic third ventriculostomy (ETV) is a well-accepted treatment option instead of ventriculoperitoneal shunt placement in cases of obstructive hydrocephalus. A sufficient flow from the ventricles to the basal cisterns requires perforation of the arachnoid membranes in the retroclival region. This point is critical to achieve an optimal outcome. The complex arachnoid relations were investigated in the retroclival region from the viewpoint of ETV, and anatomic landmarks were defined for subarachnoid dissections. METHODS: Sixty fresh human cadaveric specimens were dissected under macroscopic, microscopic, and endoscopic control. The recordings of 100 operated cases of ETVs were analyzed to ascertain the clinical-anatomic relevance. RESULTS: The Liliequist membrane complex and the anterior pontine membranes are located just above and parallel to both sides of the basilar artery. The basal attachment of these membranes forms an inverted U-shaped, white-grey thickening on the outer arachnoid. We refer to this structure as the clival line. During ETV, if arachnoid dissections were performed ventrally to the clival line, the outer arachnoid was opened; this resulted in a limited flow to the subarachnoid spaces (ventriculo-subdural). If the perforation on the arachnoid membranes was dorsal to the clival line, the prepontine cistern could be directly reached through the Liliequist membrane complex. CONCLUSIONS: Sufficient arachnoid dissection is essential for a successful ETV. The clival line is an important landmark that helps to perform the subarachnoid dissections correctly and achieve an undisrupted cerebral spinal fluid flow between the ventricles and the basal cisterns.
EVALuna2:214797